To find 6x7 using 3x7, you can simply double the result of 3x7. This is because multiplication is distributive over addition, meaning that multiplying a number by a sum is the same as multiplying the number by each addend and then adding the products. In this case, 6x7 can be thought of as (3+3)x7, which equals 3x7 + 3x7, or 21 + 21, which equals 42.
it i s eather 1X21 11X11 and
y = -1/(3x7 + 2x - 9)y = -(3x7 + 2x - 9)-1y' = -(-1)(3x7 + 2x - 9)-2(3x7 + 2x - 9)'y' = (3x7 + 2x - 9)-2(21x6 + 2)y' = (21x6 + 2)/(3x7 + 2x - 9)2
3x7 = 21
1 x 7 plus 2 x 7 is the same as 3 x 7
22
3 x 7 = 3 x (5 + 2) And since multiplication is distributive over addition, 3 x (5 + 2) = 3 x 5 + 3 x 2
We don't know and can't calculate it, until we're given the value of 'x'.
133
41
To find 6x7 using 3x7, you can simply double the result of 3x7. This is because multiplication is distributive over addition, meaning that multiplying a number by a sum is the same as multiplying the number by each addend and then adding the products. In this case, 6x7 can be thought of as (3+3)x7, which equals 3x7 + 3x7, or 21 + 21, which equals 42.
2x7 = 14 x7 = 7 3x7 = 3*7 = 21
it i s eather 1X21 11X11 and
y = -1/(3x7 + 2x - 9)y = -(3x7 + 2x - 9)-1y' = -(-1)(3x7 + 2x - 9)-2(3x7 + 2x - 9)'y' = (3x7 + 2x - 9)-2(21x6 + 2)y' = (21x6 + 2)/(3x7 + 2x - 9)2
It is: 5+(3*7) = 26
-50, first you do 3x7=21x(-2)=-42 then 8-(-42)=-50
3x7 = 21